Control and management of a DC energy grid - Nurulhuda Abdul Rahman. (2011)
An energy grid would consist of multiple sources and loads, and for future grids, chances of realizing them in dc are high. Therefore, a project is proposed here to investigate the control and management of dc energy grids, and their co-existence with ac energy grids. An optimum design and control of three-phase grid-connected photovoltaic and wind turbine energy system has been proposed and analyzed. Finally, with the help of embedded MATLAB function, Simulink and PowerSim software the article succeeds to achieve the desired control output and have a good management system. Simulation results show the accuracy of the photovoltaic and wind turbine model which shows their performance and characteristics.